ANALISA PROSES KOMUNIKASI ATAS NORMALISASI KONSEP PANOPTICON DALAM ORGANISASI BHAYANGKARI - Bulandari, Phopy Harjanti (Interaksi: Jurnal Ilmu Komunikasi, 2018)
This article discusses the panopticon mechanism happened in Bhayangkari – an organization of wives of police in Indonesia. By using case study, this article focuses to see the system and the role of mode of communication that done by members of Bhayangkari. Theory of symbolic violence applied to explain how women were controlled and were became the victim of the panopticon in this organization. This research found that women in Bhayangkari proud to be controlled and pressed under the normative role of the organization with patriarchal culture. It is reflected in the way they wear dress, how they conduct vertical communication, as well as how they express themselves in social media. Furthermore, those particular behaviors were done in order to gain prestige and pride of Bhayangkari woman. Finally, this research concluded that Bhayangkari women did not realize that the practice of panopticon mechanism happened in their organization. They did not aware that patriarchy culture has controlled them and defined them as the victim of symbolic violence.